Healthcare-Associated Infections: Trends and Prevention Prospectives - E. B. Brusina; O. V. Kovalishena; A. M. Tsigelnik (Эпидемиология и вакцинопрофилактика)
Here we discuss the recent trends in developing surgical technologies, their impact on the incidence of healthcare associated infections (HAIs), and approaches for the efficient infection control. Features of the contemporary surgery include permanent increase in the number of minimally invasive interventions, implants, and transplants, ongoing development of surgical equipment, and constant improvement in anesthesiology techniques, along with the decrease in use of natural suture materials and length of hospital stay all resulting in a significant decline in the incidence of HAIs. Perioperative use of antimicrobial agents, refusal of preoperative shaving, implementation of barrier methods, and improvement in sterilization also contributed to this trend. However, the risk of severe complications significantly increased, and the multidrug-resistant microorganisms became widespread. Currently, permanent monitoring and risk assessment are the main approaches to overcome these problems.